Development and Validation of the General-Purpose PlayfulQuest Scale : Investigating Playfulness in Dating App Use - Tuuri, Kai; Vahlo, Jukka (United States, 2026)
Play and playfulness are usually considered inherent characteristics of an exploring and self-actualizing human being. Although play and its forms of manifestation in human activity and development have been studied for decades, measuring instruments regarding playfulness are still rare. The existing instruments mainly focus on trait-based approach while playfulness in the dynamic processes of contextual engagement has remained largely unaddressed. In this study, a novel psychometric scale PlayfulQuest was developed and validated with Finnish survey data (N=2,278). The scale measures perceived playfulness of contextual engagement in three factors: Immersive Focus, Autotelic Priority, and Non-Real Framing. The scale development was carried out in the context of dating activities, with a particular focus on dating app use. Autotelic Priority appeared as a strongest predictor of playful approach, while Non-Real Framing was identified as the main predictor of perceiving the app use in terms of game-like experience. It was also revealed that the nonusers of dating apps demonstrated higher scores in the all three factors of playfulness in comparison to the group of dating app users. Although the validation of the scale is done in the dating context, it is designed to function as a general-purpose instrument for studying playful engagement across varying contextual activities, regardless of whether they are considered gaming, play, or something else.
Mindtrek '25: Proceedings of the 28th International Academic Mindtrek